A high-energy plasma sprayed multiphase titania composite coating, a preparation method and application thereof

CN122879638APending Publication Date: 2026-10-09XI AN JIAOTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611148470.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种高能等离子喷涂多相氧化钛复合涂层及制备方法和应用,以解决现有TiC基涂层脆性大、耐蚀性不足以及TiC与TiO2粉末复合不均匀、涂层结合强度低的技术问题

Benefits of technology

本发明公开了一种高能等离子喷涂多相氧化钛复合涂层的制备方法,通过将TiC粉末球磨细化后与TiO2粉末混合球磨、加入粘结剂低速球磨后经喷雾造粒获得TiC-TiO2球形粉末,并在预处理基体表面制备金属粘结层后采用等离子喷涂沉积复合涂层,利用等离子喷涂过程中TiC与TiO2的原位氧化还原耦合反应形成以TiO为主相、含TiO2和TiOx相的多相复合涂层。通过分步球磨工艺解决了TiC与TiO2因粒径差异大、TiO2浆料黏度大而导致的直接混合易分层和团聚的技术难题,获得了球形度好、流动性优异的复合粉末;同时利用TiC的还原性与TiO2的含氧特性,在等离子喷涂高温射流中发生原位化学反应,形成区别于传统物理混合沉积的TiO/TiO2/TiOx多相结构,其中TiO和TiOx作为氧缺位相可与TiO2稳定相共同构成多相界面,有利于裂纹偏转和磨损能量耗散,TiO2相则提高涂层在腐蚀介质中的化学稳定性,配合金属粘结层的连接缓解热膨胀失配,从而使涂层兼具高结合强度、优异耐磨性和耐腐蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a high-energy plasma sprayed multiphase titanium oxide composite coating and a preparation method and application thereof, and belongs to the technical field of surface protection of thermal spraying coating. The method comprises the following steps: after TiC powder is finely ground by ball milling, TiO2 powder is added to mix and ball mill, a binder is added to ball mill at low speed to obtain a spray granulation slurry, and TiC-TiO2 spherical powder is obtained through spray granulation, drying and screening; the surface of a substrate is subjected to sand blasting roughening and cleaning treatment, and a bonding layer is prepared on the surface, and then the TiC-TiO2 spherical powder is deposited by using a plasma spraying process, so that TiC and TiO2 are subjected to in-situ oxidation-reduction coupling reaction in a high-temperature plasma jet, and a multiphase composite coating mainly containing TiO, rutile type and / or anatase type TiO2 and non-stoichiometric TiO x phases is formed. Through the TiO, TiO2 and TiO x multiphase synergy and the connection of the bonding layer, the anti-abrasion, corrosion resistance and anti-peeling capacity under the working conditions of containing solid particles, corrosive medium and the like are improved, and the application is suitable for surface protection of valve parts and wear-resistant and corrosion-resistant components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermal spray coating surface protection technology, specifically relating to a high-energy plasma sprayed multiphase titanium oxide composite coating, its preparation method, and its application. Background Technology

[0002] Valves are critical fluid control components in petrochemical, marine engineering, slurry transportation, and energy equipment, typically subjected to the combined effects of media erosion, abrasive wear, localized corrosion, and sliding wear. Scratches, peeling, corrosion pits, or localized out-of-roundness on the sealing surface can easily lead to internal leakage, increased opening and closing torque, and reduced service life. Currently, valve protection commonly employs cobalt-based and nickel-based alloy weld overlays, hard coatings such as WC-CoCr, Cr3C2-NiCr, Cr2O3, and TiO2, or ceramic coatings. Among them, metal overlay has certain bonding strength and wear resistance, but may have problems such as high heat input, high dilution rate, high cost, or insufficient adaptability to complex media; carbide coatings such as WC-CoCr are suitable for wear conditions, but their stability in some highly corrosive media or high-temperature oxidizing environments still needs to be comprehensively considered; ceramic coatings such as Cr2O3 and TiO2 have good corrosion resistance and wear resistance potential, but the porosity of the layered structure of ceramic coatings, unmelted particles, interlayer cracks, and thermal expansion mismatch between the coating and the metal substrate may cause the coating to crack and peel off under impact, thermal cycling, or sliding conditions of the sealing pair.

[0003] Titanium carbide (TiC) is widely used as a hard wear-resistant coating material in mechanical parts, cutting tools, and other fields due to its low density, high hardness, high melting point, good wear resistance, and chemical stability. However, as a ceramic material mainly composed of covalent bonds, TiC is inherently brittle and lacks toughness. Under impact or high load conditions, it is prone to cracking or even brittle fracture, severely limiting the service life and reliability of the coating. TiO2 has good chemical stability and corrosion resistance, making it suitable for use in thermal spray ceramic coatings. Introducing TiO2 into TiC-based coatings is expected to improve the coating's crack propagation resistance and corrosion resistance by leveraging the stable oxide characteristics of TiO2, building upon the wear-resistant properties of the TiC hard phase. However, TiO2 powder, especially rutile TiO2 powder, has high viscosity in water-based slurries. Furthermore, there are differences in particle size, density, and melting behavior between TiC and TiO2. Simple mechanical mixing can easily lead to agglomeration, delamination, and uneven granulation, resulting in uneven heating during spraying, a large number of unmelted particles, increased coating porosity, and insufficient structural stability. On the other hand, TiC and TiO2 are not simply deposited as an inert physical mixture in high-temperature plasma jets. TiC has reducing properties, and TiO2 can act as an oxygen-containing component. Under high-temperature, high-speed plasma jet conditions and localized reducing environments, in-situ redox coupling reactions can occur to generate TiO and non-stoichiometric TiO2. xAnd the carbon-deficient TiC phase structure. If the spherical powder structure of TiC-TiO2, the crystal form and amount of TiO2, and the plasma spraying power window can be controlled, the coating can form a TiO2-dominant phase containing TiO2 and TiO2. x The multiphase composite structure is expected to yield valve protection coatings that differ from single TiC or single TiO2 coatings.

[0004] Therefore, developing a TiC-TiO2 spherical powder suitable for valve sealing surfaces and other components, and its plasma spraying preparation method, through uniform powder compounding, metal bonding layer connection, and in-situ phase structure control during the spraying process, to obtain a TiO-titanium oxide multiphase composite coating, has practical significance and application value for improving the bonding strength and corrosion resistance of traditional valve ceramic coatings. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a high-energy plasma spraying multiphase titanium oxide composite coating, its preparation method and application, so as to solve the technical problems of high brittleness, insufficient corrosion resistance, uneven composite of TiC and TiO2 powder and low coating bonding strength of existing TiC-based coatings.

[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating, comprising: ball milling TiC powder to refine it, mixing it with TiO2 powder and ball milling it, adding a binder and ball milling it at low speed to obtain a spray-granulated slurry; spray granulating, drying and sieving to obtain TiC-TiO2 spherical powder; preparing a metal binder layer on the pretreated substrate surface, and using a plasma spraying process to deposit the TiC-TiO2 spherical powder onto the surface of the metal binder layer to obtain a high-energy plasma-sprayed multiphase titanium dioxide composite coating; During plasma spraying, TiC and TiO2 undergo an in-situ redox coupling reaction, forming a TiO2-based main phase containing TiO2 and TiO2. x Multiphase composite coatings; of which, 1 <x<2。

[0007] Preferably, the particle size of TiC powder is 1~5 μm; the particle size of TiO2 powder is 0.1~2 μm; and the TiO2 powder accounts for 10%~40% of the total mass of TiC powder and TiO2 powder.

[0008] Preferably, the TiC-TiO2 spherical powder has a particle size of 15~53 μm and a loose packing density of 1.0-1.2 g / cm³. 3 The powder flowability is 12-18 s / 50g.

[0009] Preferably, the ball milling speed for TiC refining is 300-500 r / min, and the ball milling time is 6-8 h; the ball milling time after adding TiO2 powder is 1-4 h; the ball milling speed for low-speed ball milling after adding binder is 150-250 r / min, and the ball milling time is 2-4 h; the binder is polyvinyl alcohol or polyethylene glycol, and the mass of the binder is 1%-2% of the total mass of TiC powder and TiO2 powder, and the mass concentration of the binder is 40%-50%.

[0010] Preferably, the conditions for spray granulation include: an inlet air temperature of 170~200℃, a centrifugal frequency of 260~280 Hz, and a feed rate of 20~30 RPM.

[0011] Preferably, the substrate is steel, high-temperature alloy or titanium alloy; the pretreatment of the substrate includes: sandblasting roughening and cleaning the substrate before spraying, and preheating the substrate to 300~450℃; The conditions for sandblasting roughening include: sandblasting air pressure of 0.3±0.05 MPa, sandblasting angle of 70±10°, and distance between the spray gun and the substrate surface of 100~150 mm.

[0012] Preferably, the metal bonding layer is a NiCr bonding layer, and the thickness of the metal bonding layer is 50~100 μm.

[0013] Preferably, the parameters of the plasma spraying process include: current of 300-400 A, voltage of 120-160 V, and argon flow rate of 150-220 L·min. -1 The hydrogen flow rate is 6-10 L·min -1 The spraying distance is 100-120 mm, and the powder feeding rate is 5-10 g·min. -1 .

[0014] The present invention discloses a high-energy plasma-sprayed multiphase titanium oxide composite coating, which is prepared by the above-mentioned high-energy plasma-sprayed multiphase titanium oxide composite coating preparation method. The bonding strength of the high-energy plasma-sprayed multiphase titanium oxide composite coating is 46.4~65.8 MPa.

[0015] The present invention discloses the application of the above-mentioned high-energy plasma sprayed multiphase titanium oxide composite coating in the surface protection of valve components, wear-resistant and corrosion-resistant components, marine equipment components or corrosion-wear coupled working conditions.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating. The method involves ball milling TiC powder to refine it, then mixing and ball milling it with TiO2 powder, adding a binder, ball milling at low speed, and finally spray granulation to obtain TiC-TiO2 spherical powder. A metal binder layer is prepared on a pretreated substrate surface, followed by plasma spraying to deposit the composite coating. The in-situ redox coupling reaction between TiC and TiO2 during plasma spraying forms a TiO2-dominant phase, containing TiO2 and TiO2. x A multiphase composite coating was developed. A stepwise ball milling process was used to overcome the technical challenges of easy stratification and agglomeration when directly mixing TiC and TiO2 due to their large particle size differences and the high viscosity of TiO2 slurry, resulting in a composite powder with good sphericity and excellent flowability. Simultaneously, utilizing the reducing properties of TiC and the oxygen-containing characteristics of TiO2, an in-situ chemical reaction occurred during high-temperature plasma spraying, forming a TiO / TiO2 / TiO2 composite coating that differs from traditional physical mixing deposition. x Multiphase structure, in which TiO and TiO x As an oxygen-deficient phase, it can form a multiphase interface together with the TiO2 stable phase, which is beneficial to crack deflection and wear energy dissipation. The TiO2 phase improves the chemical stability of the coating in corrosive media and, together with the metal bonding layer, alleviates thermal expansion mismatch, thus enabling the coating to have high bonding strength, excellent wear resistance and corrosion resistance.

[0017] This invention discloses a high-energy plasma-sprayed multiphase titanium dioxide composite coating, wherein the phase composition of the composite coating is a TiO main phase, a TiO2 secondary phase, and a non-stoichiometric TiO2 phase. x This multiphase composite structure exhibits coexisting phases and is a direct product of the in-situ redox coupling reaction between TiC and TiO2 in a high-temperature plasma jet. The multiphase interface can deflect and passivate propagating cracks and dissipate wear energy, while the TiO2 phase provides chemical stability to block corrosive media. x The oxygen-deficient structure of the phase imparts a certain degree of electronic conductivity to the coating. The uniform composite powder obtained by stepwise ball milling ensures consistent composition of the molten droplets, and the multiphase interface generated by in-situ reaction enhances the coating's cohesion, while the stress buffering effect of the metal bonding layer. The bonding strength of 46.4~65.8 MPa is far superior to the level of traditional plasma-sprayed ceramic coatings, which is usually no higher than 30 MPa.

[0018] This invention discloses the application of high-energy plasma-sprayed multiphase titanium dioxide composite coatings in the surface protection of valve components, wear-resistant and corrosion-resistant components, marine equipment components, or surfaces subjected to coupled corrosion and wear. Valve sealing surfaces are subjected to multiple effects during service, including media erosion, abrasive wear from solid particles, localized corrosion, and sliding wear of the sealing pair. Traditional cobalt-based / nickel-based weld overlays suffer from high heat input, high cost, and insufficient stability in corrosive media, while single oxide ceramic coatings suffer from low bonding strength and easy peeling. The multiphase synergistic mechanism of the high-energy plasma-sprayed multiphase titanium dioxide composite coating of this invention involves the TiO main phase contributing to hardness and wear resistance, the TiO2 phase contributing to corrosion resistance and chemical stability, and the TiO2 phase contributing to... x It contributes to crack passivation and energy dissipation, and combined with the high bonding strength of the metal bonding layer, it has unique protective advantages under coupled conditions of opening and closing sliding, erosion of solid particles and corrosive media. The bonding strength is 46.4~65.8 MPa, providing an optional solution for surface protection of long-life and high-reliability components such as valves and marine equipment. Attached Figure Description

[0019] Figure 1 SEM images of TiC-30 wt% rutile TiO2 spherical powders prepared in Examples 3 and 5 of this invention; wherein, (a) is the powder morphology image of Example 3, and (b) is the powder morphology image of Example 5; Figure 2 The XRD pattern of TiC-30 wt% rutile TiO2 spherical powder prepared in Example 3 of this invention; Figure 3 The images show the cross-sectional morphology of the high-energy plasma-sprayed multiphase titanium oxide composite coating prepared in Example 10 of this invention; where (a) is a SEM image of the coating cross-section at 400x magnification; and (b) is a SEM image of the coating cross-section at 800x magnification. Figure 4 The XRD patterns of the high-energy plasma-sprayed multiphase titanium oxide composite coatings prepared in Examples 9-11 of this invention and the powders used thereon; Figure 5 Comparison of tensile bond strength of high-energy plasma-sprayed multiphase titanium oxide composite coatings prepared in Examples 6-11 of this invention. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.

[0022] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.

[0023] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.

[0024] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.

[0025] In this invention, unless otherwise specified, the numerical range "a~b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation for these numerical combinations.

[0026] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.

[0027] The term “and / or” as used in this invention refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.

[0028] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.

[0029] To overcome the problems of corrosion failure, interlayer peeling, and sealing failure that easily occur in existing valve protective coatings under corrosion-wear coupling conditions, the present invention aims to provide a method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating for valve protection and its application. This method uses TiC and TiO2 as raw materials, obtaining uniformly composite spherical agglomerated powder through stepwise ball milling and spray granulation, and utilizing the in-situ redox coupling reaction during plasma spraying to construct a TiO / TiO2 / TiO2 composite coating. x A multiphase synergistic coating, where x has a specific value between 1 and 2.

[0030] The present invention provides a method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating, comprising the following steps: Step 1: Prepare the slurry. Crush TiC into powder and mix it with deionized water. Then, use a planetary ball mill for high-speed ball milling at a speed of 300-500 r / min for 6-8 h to reduce the particle size of TiC and improve its particle size matching with TiO2, thus obtaining refined TiC powder. Subsequently, add TiO2 powder and mix and ball mill for 1-4 h to obtain TiC-TiO2 mixed powder. After adding a binder, ball mill at low speed to uniformly disperse TiC and TiO2 in the slurry, thus obtaining the spray granulation slurry.

[0031] The binder is first stirred with a portion of deionized water at 90℃ for 2 hours to fully dissolve the binder in the deionized water, resulting in a TiC / TiO2 / binder mixture. The TiC / TiO2 solid phase content (by mass) in the mixture is 40%–50%, with TiO2 accounting for 10–40 wt% of the solid phase content. The binder content (by mass) is 1–2% of the solid phase mass, and the binder is polyvinyl alcohol or PEG. The TiC powder has a particle size of 1–5 μm, and the TiO2 powder has a particle size of 0.1–2 μm. The mixture is then ball-milled at low speed using a planetary ball mill at a speed of 150–250 r / min for 2–4 hours to obtain a uniformly dispersed spray-granulated slurry.

[0032] Step 2: Prepare spherical powder; use a centrifugal spray granulation dryer to spray granulate, dry and sieve the spray granulation slurry to prepare spherical powder, and obtain TiC-TiO2 spherical powder.

[0033] This TiC-TiO2 spherical powder is suitable for high-energy plasma spraying processes with a wide velocity range and exhibits good flowability. The process parameters for the centrifugal spray granulation dryer are: inlet air temperature 170-200℃, centrifugal frequency 260-280Hz, and feed rate 20-30RPM. After drying and sieving, the powder yields particles with a diameter of 15-53μm and a bulk density of 1.0-1.2g / cm³. 3 TiC-TiO2 spherical powder with a flowability of 12-18s / 50g.

[0034] Step 3: Pre-treatment of the substrate before spraying: The surface of the stainless steel substrate is sandblasted and cleaned. The sandblasting material is No. 22 white corundum abrasive, the sandblasting air pressure is 0.3±0.05 MPa, the sandblasting angle is 70±10°, and the distance between the spray gun and the surface of the stainless steel substrate is 100-150 mm. The substrate surface is cleaned with alcohol. The substrate can be steel, high-temperature alloy, or titanium alloy.

[0035] Step four: Using wide-velocity-range high-energy plasma spraying technology, TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate to prepare a high-energy plasma-sprayed multiphase titanium oxide composite coating. First, the stainless steel substrate treated in step two is preheated to a temperature of 300-450 ℃ without powder feeding using a wide-velocity-range high-energy plasma spraying process. Then, a 50-100 μm NiCr bonding layer is deposited on the substrate using the wide-velocity-range high-energy plasma spraying process. Next, the TiC-TiO2 spherical powder obtained in step two is placed in a plasma spraying powder feeding device, and the high-energy plasma spraying multiphase titanium oxide composite coating is obtained on the substrate by adjusting the plasma spraying process parameters using a wide-velocity-range high-energy plasma spraying process.

[0036] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 300-400 A, voltage 120-160 V, and argon gas flow rate 150-220 L / min. -1 The flow rate of secondary hydrogen gas is 6-10 L·min. -1 The spraying distance is 100-120mm, and the powder feeding rate is 5-10 g·min. -1 The coating thickness is 100-200μm.

[0037] The TiC-TiO2 spherical powder prepared by spray granulation consists of a TiC phase and rutile TiO2, with fine TiO2 powder embedded between TiC particles. The plasma-sprayed TiO2-titanium oxide multiphase composite coating consists of a TiO phase, TiO2, and TiO2. x Phase composition.

[0038] Specifically, this invention discloses a method for preparing TiC-TiO2 spherical powder, comprising: pre-ball milling TiC powder to obtain refined TiC powder; then adding TiO2 powder to the refined TiC powder for mixed ball milling to obtain a TiC-TiO2 mixture; adding a binder and ball milling at low speed to uniformly disperse TiC and TiO2 in the slurry to obtain a spray granulation slurry; subsequently, spray granulating, drying, and sieving the spray granulation slurry to obtain TiC-TiO2 spherical powder.

[0039] The TiC-TiO2 spherical powder prepared by spray granulation contains two phases: TiC and rutile TiO2. The coating prepared also contains the rutile TiO2 phase.

[0040] Both TiC and TiO2 powders are crushed powders. The particle size of crushed TiC powder is 1-5 μm, the particle size of TiO2 powder is 0.1-2 μm, and the particle size of TiC-TiO2 spherical powder is 15-53 μm. The loose packing density of the powders is 1.0-1.2 g / cm³. 3The powder flowability is 12-18 s / 50g.

[0041] TiO2 powder accounts for 10% to 40% of the total mass of TiC powder and TiO2 powder. The TiO2 powder can be rutile TiO2 or anatase TiO2. Considering that rutile TiO2 has higher thermal stability, rutile TiO2 is preferred.

[0042] The binder is polyvinyl alcohol or PEG; the mass of the binder is 1%-2% of the mass of the solid phase; the mass percentage of the solid phase is 40%-50% of the mass of the mixture; the ball milling time is 8-12 h.

[0043] TiC powder is first ball-milled at 300-500 r / min for 6-8 h to reduce the particle size of TiC and improve its particle size matching with TiO2. Then, TiO2 powder is added and ball-milled for 1-4 h to allow TiO2 to enter the gaps between TiC particles and form a uniform composite. Finally, binders such as PVA are added and ball-milled at 150-250 r / min for 2-4 h to avoid agglomeration and slurry instability caused by the high viscosity of TiO2.

[0044] The inlet temperature of spray granulation is 170-200 ℃; centrifugation is 260-280 HZ, feed is 20-30 RPM, and outlet air temperature is 130-150 ℃.

[0045] This invention also discloses a method for preparing a high-energy plasma-sprayed multiphase titanium oxide composite coating, comprising: roughening and cleaning the substrate by sandblasting; preparing a NiCr or other metal bonding layer on the substrate surface as a bonding layer; and using a high-energy plasma spraying process, first spraying the bonding layer on the substrate, and then spraying TiC-TiO2 spherical powder on the surface of the bonding layer, so that TiC and TiO2 undergo an in-situ redox coupling reaction during the plasma spraying process, thereby forming a TiO-titanium oxide multiphase composite coating on the substrate surface.

[0046] The substrate is made of steel, high-temperature alloy or titanium alloy. Before spraying, the substrate is roughened and cleaned by sandblasting and preheated to 300-450 ℃.

[0047] The conditions for sandblasting roughening include: using No. 22 white corundum sand as the sandblasting material, sandblasting air pressure of 0.3±0.05 MPa, sandblasting angle of 70±10°, and distance between the spray gun and the substrate surface of 100-150 mm.

[0048] The thickness of the sprayed adhesive layer is 50-100 μm.

[0049] The parameters for plasma spraying include: current of 300-400 A, voltage of 120-160 V, and argon flow rate of 150-220 L·min.-1 The hydrogen flow rate is 6-10 L·min -1 The spraying distance is 100-120 mm, and the powder feeding rate is 5-10 g·min. -1 .

[0050] The plasma-sprayed composite coating has a layered mosaic structure; the coating includes a TiO main phase, rutile and / or anatase TiO2 secondary phases, and non-stoichiometric TiO2. x The phase may also include a carbon-deficient TiC phase in some embodiments; the thickness of the plasma-sprayed TiC-TiO2 composite coating is 100-200 μm.

[0051] The high-energy plasma-sprayed multiphase titanium dioxide composite coating disclosed in this invention comprises TiO, TiO2, and non-stoichiometric TiO2. x The coating is a multiphase layer-by-layer stacked and inlaid structure; the bonding strength of the plasma-sprayed TiO-titanium oxide multiphase composite coating is 46.4-65.8 MPa.

[0052] This invention discloses the application of the above-mentioned high-energy plasma sprayed multiphase titanium dioxide composite coating in valve components such as pumps, ball valves, and control valves, wear-resistant and corrosion-resistant components, marine equipment components, or surface protection under corrosion and wear coupling conditions.

[0053] This invention does not simply prepare a TiC / TiO2 physically mixed coating, but rather utilizes the in-situ redox coupling reaction of TiC and TiO2 during high-energy plasma spraying to form a TiO main phase, a TiO2 secondary phase, and a non-stoichiometric TiO2 phase in the coating. x Multiphase structures with coexisting phases. TiO and TiO x As an oxygen-deficient titanium oxide phase, the TiO2 phase can form a multiphase interface together with the stable TiO2 phase, which is beneficial for crack deflection, crack passivation and wear energy dissipation; the TiO2 phase is beneficial for improving the chemical stability and barrier effect of the coating in corrosive media.

[0054] This invention employs a stepwise powder preparation route of "TiC pre-ball milling, TiO2 addition and mixing, PVA addition for low-speed homogenization, and spray granulation," which solves the problems of large particle size differences between TiC and TiO2, high viscosity of TiO2 slurry, and easy stratification and agglomeration when directly mixed. The prepared TiC-TiO2 spherical powder has good sphericity and powder feeding stability, providing a powder foundation for subsequent uniform plasma spraying deposition. By controlling the TiO2 addition amount and spraying power window, TiO2 can play a toughening and corrosion-resistant role in both the powder and the coating, while avoiding excessive unmelted particles that would increase coating porosity. In particular, under the powder condition of 30 wt% TiO2 addition, the sprayed coating quality is good, and the coating bonding strength is 46.4-65.8 MPa.

[0055] The rutile titanium oxide prepared by this invention possesses high hardness and toughness, and is thermodynamically the most stable crystal form. Its phase composition remains stably dominated by the high-hardness rutile phase before and after spraying, avoiding the unfavorable phase transformation that may occur when the micron-sized powder completely melts and then solidifies. The high-temperature, high-speed flight behavior of the composite powder can significantly improve the coating density, increasing the bonding strength of traditional plasma-sprayed ceramic coatings from no more than 30 MPa to 65.8 MPa.

[0056] This invention employs conventional plasma spraying equipment and a metal binder preparation route commonly used in the valve industry. It does not require the introduction of large amounts of Co, Ni, or other metal binder phases as the coating substrate, nor does it require complex subsequent high-temperature annealing treatment. It has the advantages of a clear process route, suitability for deposition on the surface of complex valve parts, and industrial application.

[0057] This invention utilizes a TiO-titanium oxide multiphase composite coating for the surface protection of valve sealing surfaces and flow-through components. Compared to wear-resistant coatings for simple mechanical parts, this invention addresses practical problems such as sliding wear of valve sealing surfaces, erosion by solid particles, corrosion by corrosive media, and seal failure. Through the composite structure of a ceramic multiphase top layer and a binder layer, it improves the service stability of the coating system during valve opening and closing and media scouring processes.

[0058] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0059] Example 1 A method for preparing TiC-TiO2 spherical powder includes the following steps: Step 1: Mix TiC crushed powder and deionized water, and ball mill at high speed using a planetary ball mill at 350 r / min for 6 hours. Then, add TiO2 powder and mix for 2 hours. Next, add a binder, which is first stirred with a portion of the deionized water at 90°C for 2 hours to fully dissolve the binder, resulting in a mixture. The solid content (by mass) of the mixture is 40%, of which TiO2 accounts for 10 wt% of the solid content, and the binder content (by mass) is 1 wt% of the solid mass. The binder is polyvinyl alcohol. The TiC crushed powder has a particle size of 1-5 μm, and the TiO2 powder has a particle size of 0.1-2 μm. Then, ball mill the mixture at low speed using a planetary ball mill at 250 r / min for 4 hours to obtain a uniformly dispersed slurry.

[0060] Step two: Preparation of spherical powder; Spherical powder is prepared using a centrifugal spray granulation dryer to obtain TiC-TiO2 spherical powder. This TiC-TiO2 spherical powder is suitable for wide-range high-energy plasma spraying processes and has good flowability. The process parameters of the centrifugal spray granulation dryer are: inlet air temperature 200℃, centrifugal frequency 280Hz, and feed rate 30RPM. After drying, the powder is sieved to obtain a particle size of 40-53μm and a loose powder density of 1.03g / cm³. 3 TiC-TiO2 spherical powder with a powder flowability of 17.68s / 50g.

[0061] Example 2 A method for preparing TiC-TiO2 spherical powder includes the following steps: Step 1: Mix TiC crushed powder and deionized water, and ball mill at high speed using a planetary ball mill at 450 r / min for 6 hours. Then, add TiO2 powder and mix for 2 hours. Next, add a binder, which is first stirred with a portion of the deionized water at 90°C for 2 hours to fully dissolve the binder, resulting in a mixture. The solid content (by mass) of the mixture is 50%, of which TiO2 accounts for 20 wt% of the solid content, and the binder content (by mass) is 1 wt% of the solid mass. The binder is polyvinyl alcohol. The particle size of the TiC crushed powder is 1-5 μm, and the particle size of the TiO2 powder is 0.1-2 μm. Then, ball mill the mixture at low speed using a planetary ball mill at 150 r / min for 2 hours to obtain a uniformly dispersed slurry.

[0062] Step two: Preparation of spherical powder; Spherical powder, TiC-TiO2, is prepared using a centrifugal spray granulation dryer. This TiC-TiO2 spherical powder is suitable for wide-range high-energy plasma spraying processes and exhibits good flowability. The process parameters of the centrifugal spray granulation dryer are: inlet air temperature 190℃, centrifugal frequency 260Hz, and feed rate 25RPM. After drying, the powder is sieved to obtain a particle size of 26-53μm and a loose powder density of 1.09 g / cm³. 3 TiC-TiO2 spherical powder with a powder flowability of 16.57s / 50g.

[0063] Example 3 A method for preparing TiC-TiO2 spherical powder includes the following steps: Step 1: Mix TiC crushed powder and deionized water, and ball mill at high speed using a planetary ball mill at 400 r / min for 8 hours. Then, add TiO2 powder and mix for 4 hours. Next, add a binder, which is first stirred with a portion of the deionized water at 90°C for 2 hours to fully dissolve the binder, resulting in a mixture. The solid content (by mass) of the mixture is 50%, of which TiO2 accounts for 30 wt% of the solid content, and the binder content (by mass) is 2 wt% of the solid mass. The binder is polyvinyl alcohol. The TiC crushed powder has a particle size of 1-5 μm, and the TiO2 powder has a particle size of 0.1-2 μm. Then, ball mill the mixture at low speed using a planetary ball mill at 200 r / min for 3 hours to obtain a uniformly dispersed slurry.

[0064] Step two: Preparation of spherical powder; Spherical powder, TiC-TiO2, is prepared using a centrifugal spray granulation dryer. This TiC-TiO2 spherical powder is suitable for wide-range high-energy plasma spraying processes and exhibits good flowability. The process parameters of the centrifugal spray granulation dryer are: inlet air temperature 175℃, centrifugal frequency 275Hz, and feed rate 20RPM. After drying, the powder is sieved to obtain a particle size of 15-53μm and a loose powder density of 1.13g / cm³. 3 TiC-TiO2 spherical powder with a powder flowability of 13.48s / 50g.

[0065] Example 4 A method for preparing TiC-TiO2 spherical powder includes the following steps: Step 1: Mix TiC crushed powder and deionized water, and ball mill at high speed using a planetary ball mill at 500 r / min for 7 hours. Then, add TiO2 powder and mix for 3 hours. Next, add a binder, which is first stirred with a portion of the deionized water at 90°C for 2 hours to fully dissolve the binder, resulting in a mixture. The solid content (by mass) of the mixture is 40%, of which TiO2 accounts for 30 wt% of the solid content, and the binder content (by mass) is 2 wt% of the solid mass. The binder is polyvinyl alcohol. The TiC crushed powder has a particle size of 1-5 μm, and the TiO2 powder has a particle size of 0.1-2 μm. Then, ball mill the mixture at low speed using a planetary ball mill at 200 r / min for 2 hours to obtain a uniformly dispersed slurry.

[0066] Step two: Preparation of spherical powder; Spherical powder, TiC-TiO2, is prepared using a centrifugal spray granulation dryer. This TiC-TiO2 spherical powder is suitable for wide-range high-energy plasma spraying processes and exhibits good flowability. The process parameters of the centrifugal spray granulation dryer are: inlet air temperature 200℃, centrifugal frequency 270Hz, and feed rate 20RPM. After drying, the powder is sieved to obtain a particle size of 30-53μm and a loose powder density of 1.11 g / cm³. 3 TiC-TiO2 spherical powder with a powder flowability of 17.43s / 50g.

[0067] Example 5 A method for preparing TiC-TiO2 spherical powder includes the following steps: Step 1: Mix TiC crushed powder and deionized water, and ball mill at high speed using a planetary ball mill at 400 r / min for 8 hours. Then add TiO2 powder and mix for 4 hours. Next, add a binder, which is first stirred with a portion of the deionized water at 90°C for 2 hours to fully dissolve the binder, resulting in a mixture. The solid content (by mass) of the mixture is 40%, of which TiO2 accounts for 30 wt% of the solid content, and the binder content (by mass) is 2 wt% of the mixture mass. The binder is polyvinyl alcohol. The TiC crushed powder has a particle size of 1-5 μm, and the TiO2 powder has a particle size of 0.1-2 μm. Then, ball mill the mixture at low speed using a planetary ball mill at 200 r / min for 3 hours to obtain a uniformly dispersed slurry.

[0068] Step two: Preparation of spherical powder; Spherical powder, TiC-TiO2, is prepared using a centrifugal spray granulation dryer. This TiC-TiO2 spherical powder is suitable for wide-range high-energy plasma spraying processes and exhibits good flowability. The process parameters of the centrifugal spray granulation dryer are: inlet air temperature 175℃, centrifugal frequency 275Hz, and feed rate 20RPM. After drying, the powder is sieved to obtain a particle size of 15-53μm and a loose powder density of 1.04g / cm³. 3 TiC-TiO2 spherical powder with a powder flowability of 16.56s / 50g.

[0069] Example 6 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step 1: Pre-treatment of the substrate before spraying: The surface of the stainless steel substrate is sandblasted and cleaned. The sandblasting material is No. 22 white corundum abrasive, the sandblasting air pressure is 0.3±0.05 MPa, the sandblasting angle is 70±10°, and the distance between the spray gun and the surface of the stainless steel substrate is 100-150 mm. The substrate surface is cleaned with alcohol. The substrate can be steel, high-temperature alloy, or titanium alloy.

[0070] Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 370℃ without powder feeding using the wide-velocity high-energy plasma spraying process. Then, a 100μm NiCr bonding layer is deposited on the substrate using the wide-velocity high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 2 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 170μm, and the composite coating has a layered mosaic structure.

[0071] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 400 A, voltage 147.5 V, and argon gas flow rate 180 L / min. -1 The flow rate of secondary hydrogen gas is 8 L / min. -1 The spraying distance is 110 mm, and the powder feeding rate is 5.4 g·min. -1 .

[0072] Example 7 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step one, same as in Example 6; Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 400℃ without powder feeding using the wide-velocity high-energy plasma spraying process. Then, a 100μm NiCr bonding layer is deposited on the substrate using the wide-velocity high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 3 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 200μm, and the composite coating has a layered mosaic structure.

[0073] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 350 A, voltage 136.7 V, and argon gas flow rate 200 L / min. -1 The flow rate of secondary hydrogen gas is 8 L / min. -1 The spraying distance is 110 mm, and the powder feeding rate is 6.9 g·min. -1 .

[0074] Example 8 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step one, same as in Example 6; Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 300℃ without powder feeding using the wide-velocity high-energy plasma spraying process. Then, a 60μm NiCr bonding layer is deposited on the substrate using the wide-velocity high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 2 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 140μm, and the composite coating has a layered mosaic structure.

[0075] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 300 A, voltage 127 V, and argon gas flow rate 220 L / min. -1 The flow rate of secondary hydrogen gas is 8 L / min. -1 The spraying distance is 110 mm, and the powder feeding rate is 6.9 g·min. -1 .

[0076] Example 9 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step 1: Pre-treatment of the substrate before spraying: The surface of the stainless steel substrate is sandblasted and cleaned. The sandblasting material is No. 22 white corundum abrasive, the sandblasting air pressure is 0.3±0.05 MPa, the sandblasting angle is 70±10°, and the distance between the spray gun and the surface of the stainless steel substrate is 100-150 mm. The substrate surface is cleaned with alcohol. The substrate can be steel, high-temperature alloy, or titanium alloy.

[0077] Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 380℃ without powder feeding using the wide-velocity high-energy plasma spraying process. Then, a 70μm NiCr bonding layer is deposited on the substrate using the wide-velocity high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 3 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 170μm, and the composite coating has a layered mosaic structure.

[0078] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 400 A, voltage 147.5 V, and argon gas flow rate 180 L / min. -1 The flow rate of secondary hydrogen gas is 8 L / min. -1 The spraying distance is 110 mm, and the powder feeding rate is 5.4 g·min. -1 .

[0079] Example 10 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step one, same as in Example 9; Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 400℃ without powder feeding using the wide-velocity high-energy plasma spraying process. Then, a 60μm NiCr bonding layer is deposited on the substrate using the wide-velocity high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 2 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 200μm, and the composite coating has a layered mosaic structure.

[0080] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 350 A, voltage 136.7 V, and argon gas flow rate 200 L / min. -1 The flow rate of secondary hydrogen gas is 8 L / min. -1 The spraying distance is 110 mm, and the powder feeding rate is 6.9 g·min. -1 .

[0081] Example 11 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step one, same as in Example 9; Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 300℃ without powder feeding using the wide-velocity high-energy plasma spraying process. Then, a 50μm NiCr bonding layer is deposited on the substrate using the wide-velocity high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 3 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 140μm, and the composite coating has a layered mosaic structure.

[0082] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 300 A, voltage 127 V, and argon gas flow rate 220 L / min. -1 The flow rate of secondary hydrogen gas is 8 L / min. -1 The spraying distance is 110 mm, and the powder feeding rate is 6.9 g·min. -1 .

[0083] Example 12 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step one, same as in Example 9; Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity-range high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 450℃ without powder feeding using the wide-velocity-range high-energy plasma spraying process. Then, a 90μm NiCr bonding layer is deposited on the substrate using the wide-velocity-range high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 3 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity-range high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 180μm, and the composite coating has a layered mosaic structure.

[0084] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 400 A, voltage 142 V, and argon gas flow rate 150 L / min. -1 The flow rate of secondary hydrogen gas is 10 L·min. -1 The spraying distance is 100 mm and the powder feeding rate is 9 g·min. -1 .

[0085] Example 13 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: Step one, same as in Example 9; Step 2: TiC-TiO2 spherical powder is sprayed onto a stainless steel substrate using wide-velocity-range high-energy plasma spraying technology to prepare a composite coating. First, the stainless steel substrate treated in Step 2 is preheated to 370℃ without powder feeding using the wide-velocity-range high-energy plasma spraying process. Then, an 80μm NiCr bonding layer is deposited on the substrate using the wide-velocity-range high-energy plasma spraying process. Next, the TiC-TiO2 composite spherical powder prepared in Example 3 is placed in the plasma spraying powder feeding device, and the TiO-titanium oxide multiphase composite coating is prepared on the substrate using the wide-velocity-range high-energy plasma spraying process with adjusted plasma spraying process parameters. The coating thickness is 170μm, and the composite coating has a layered mosaic structure.

[0086] The plasma spraying process is carried out under a reducing or inert atmosphere. The spraying parameters are: current 380 A, voltage 142.8 V, and argon gas flow rate 200 L / min. -1 The flow rate of secondary hydrogen gas is 10 L·min -1 The spraying distance is 120 mm and the powder feeding rate is 9 g·min. -1 .

[0087] Example 14 A method for preparing TiC-TiO2 spherical powder includes the following steps: TiC crushed powder and rutile TiO2 powder were mixed at a mass ratio of TiC:TiO2 = 65:35, so that TiO2 accounted for 35% of the total solid phase mass. TiC powder was mixed with deionized water and ball-milled at 400 r / min for 7 hours in a planetary ball mill for refinement. Then, TiO2 powder was added and ball-milled for 2 hours. Next, polyethylene glycol (PEG, 1.5% of the total solid phase mass, pre-dissolved in some deionized water at 90℃ for 2 hours) was added, and the mixture was ball-milled at 200 r / min for 3 hours in a planetary ball mill to obtain a uniformly dispersed slurry with a solid content of 45%. Granulation was performed using a centrifugal spray granulator dryer with an inlet air temperature of 180℃, a centrifugal frequency of 270 Hz, and a feed rate of 25 RPM. After drying, TiC-TiO2 spherical powder was obtained by sieving. The loose packing density of the powder was measured to be 1.0 g / cm³. 3 The fluidity is 18s / 50g.

[0088] Example 15 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: The TiC-TiO2 spherical powder prepared in Example 14 was used. The substrate was stainless steel, roughened by blasting with No. 22 white corundum abrasive before spraying (blasting pressure 0.3 MPa, blasting angle 70°, spray gun distance 120 mm), and cleaned with alcohol. The substrate was preheated to 350°C. A wide-velocity high-energy plasma spraying system was used. An 80 μm NiCr bonding layer was first deposited on the substrate surface, followed by spraying of the composite powder. The spraying process parameters were: current 300 A, voltage 120 V, argon flow rate 200 L / min, hydrogen flow rate 6 L / min, spraying distance 110 mm, and powder feed rate 5 g / min. Under the above conditions, the high-energy plasma-sprayed multiphase titanium oxide composite coating had a dense structure, good adhesion to the substrate, and a bonding strength of 48.5 MPa. XRD phase analysis of the coating showed that TiO2 was the main phase, containing TiO2 and TiO3. x Mutually.

[0089] Example 16 A method for preparing TiC-TiO2 spherical powder includes the following steps: TiC crushed powder and rutile TiO2 powder were mixed at a mass ratio of TiC:TiO2 = 60:40, so that TiO2 accounted for 40% of the total solid phase mass. TiC powder was mixed with deionized water and ball-milled at 300 r / min for 6 hours in a planetary ball mill for refinement. Then, TiO2 powder was added and ball-milled for 1 hour. Next, polyvinyl alcohol (PVA, 1.5% of the total solid phase mass, pre-dissolved in some deionized water at 90℃ for 2 hours) was added, and the mixture was ball-milled at 200 r / min for 3 hours in a planetary ball mill to obtain a uniformly dispersed slurry with a solid content of 45%. Granulation was performed using a centrifugal spray granulator dryer with an inlet air temperature of 170℃, a centrifugal frequency of 260 Hz, and a feed rate of 20 RPM. After drying, TiC-TiO2 spherical powder was obtained by sieving. The loose packing density of the powder was measured to be 1.2 g / cm³. 3 The fluidity is 12s / 50g.

[0090] Example 17 A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating includes the following steps: The TiC-TiO2 spherical powder prepared in Example 16 was used. The substrate was a titanium alloy (TC4), which was roughened by sandblasting with No. 22 white corundum abrasive before spraying (sandblasting pressure 0.3 MPa, sandblasting angle 70°, spray gun distance 120 mm), and cleaned with alcohol. The substrate was preheated to 400°C. A wide-velocity high-energy plasma spraying device was used to first deposit a 90 μm NiCr bonding layer on the substrate surface, and then the composite powder was sprayed. The spraying process parameters were: current 400 A, voltage 160 V, argon flow rate 200 L / min, hydrogen flow rate 10 L / min, spraying distance 110 mm, and powder feed rate 10 g / min. The high-energy plasma-sprayed multiphase titanium oxide composite coating prepared under the above conditions had a dense structure, good bonding with the substrate, and a bonding strength of 61.2 MPa. XRD phase analysis of the coating showed that TiO was the main phase, containing TiO2 and TiO2. x Mutually.

[0091] Figure 1 SEM images of TiC-30 wt% rutile TiO2 spherical powders prepared in Examples 3 and 5 of this invention are shown. (a) is the powder morphology image of Example 3, and (b) is the powder morphology image of Example 5. As can be seen from the images, the powders are all spherical particles with a loose and porous surface, and a particle size ranging from 15 to 53 μm. A comparison reveals that the particle size range of the powder in Example 5 is significantly smaller than that in Example 3.

[0092] Figure 2The image shows the XRD pattern of TiC-30 wt% rutile TiO2 spherical powder prepared in Example 3 of this invention. As can be seen from the image, compared with the standard PDF card, the phase of the composite powder is rutile.

[0093] Figure 3 The images show the cross-sectional morphology of the high-energy plasma-sprayed multiphase titanium oxide composite coating prepared in Example 10 of this invention; (a) is a SEM image of the coating cross-section at 400x magnification; (b) is a SEM image of the coating cross-section at 800x magnification. As can be seen from the images, the composite coating has a dense structure, consisting of a layered mosaic structure, and contains some unmelted particles. The coating thickness is estimated to be 100-200 μm. Further magnification reveals excellent interlayer bonding within the coating and its interface with the NiCr binder layer.

[0094] Figure 4 The XRD patterns of the high-energy plasma-sprayed multiphase titanium dioxide composite coatings prepared in Examples 9-11 of this invention and the powders used are shown in the figures. As can be seen from the figures, the coatings include a TiO main phase, rutile and / or anatase TiO2 secondary phases, and non-stoichiometric TiO2. x Mutually.

[0095] Figure 5 The figures show a comparison of the tensile bond strength of the high-energy plasma-sprayed multiphase titanium oxide composite coatings prepared in Examples 6-11 of this invention. As can be seen from the figures, the composite coating of Example 9 has the highest tensile bond strength, reaching 65.8 MPa, indicating that increasing the spraying power under appropriate gas flow rate is beneficial to improving the bond strength.

[0096] Table 1. Spraying parameters for high-energy plasma-sprayed multiphase titanium dioxide composite coatings prepared in Examples 6-13

[0097] The spraying parameters of the plasma-sprayed TiO-titanium oxide multiphase composite coating prepared by this invention are shown in Table 1. During the plasma spraying process, the TiC-TiO2 spherical powder undergoes rapid heating, local melting, reaction, and rapid solidification deposition. TiC, as a reducing hard ceramic phase, and TiO2, as an oxygen-containing stable oxide phase, undergo redox coupling in a localized reducing environment involving high-temperature plasma jet and hydrogen, forming TiO2 and non-stoichiometric TiO2. x The reaction occurs during powder flight and impact spreading, resulting in the co-deposition of TiO / TiO2 / TiOx phases in a layered or interlocking manner, forming a multiphase interface. This multiphase interface can alter crack propagation paths and increase crack propagation resistance; the TiO2 and TiOx phases can provide some shielding against corrosive media, reducing the risk of rapid penetration along interlayer defects in the coating; the TiO main phase and oxygen-deficient TiO2... xUnlike traditional single-TiC hard and brittle coatings, this coating is beneficial for dissipating local stress during valve opening and closing sliding and particle erosion. The NiCr binder layer is set between the substrate and the ceramic top layer, which can alleviate thermal expansion mismatch and residual stress concentration, while improving the bonding stability between the ceramic top layer and the metal substrate. The coating bonding strength reaches 65.8MPa at a high power of 59kW.

[0098] In summary, this invention discloses a high-energy plasma-sprayed multiphase titanium dioxide composite coating, its preparation method, and its application. TiC powder is pre-ball-milled to refine it, then mixed with rutile TiO2 powder and ball-milled. A binder is added, and the mixture is ball-milled at low speed to obtain a spray-granulated slurry. This slurry is then spray-granulated, dried, and sieved to obtain TiC-TiO2 spherical powder. The substrate surface is roughened and cleaned by sandblasting, and a binder layer is prepared on the substrate surface. The TiC-TiO2 spherical powder is deposited on the surface of the binder layer using a plasma spraying process. This allows TiC and TiO2 to undergo an in-situ redox coupling reaction in a high-temperature plasma jet, forming a TiO2-dominant phase containing rutile and / or anatase TiO2 and non-stoichiometric TiO2. x A multiphase composite coating was developed. Uniform composites of TiC and TiO2 powders were achieved through stepwise ball milling and spray granulation of TiC-TiO2 spherical powders. The in-situ redox coupling reaction of TiC / TiO2 was controlled by adjusting the plasma spraying power window, resulting in a multiphase composite coating with TiO2 as the main phase and containing both TiO2 and TiO2 components. x A multiphase composite coating with NiCr and other metal binders is used to improve the connection between the substrate and the ceramic top layer, thereby enhancing the bonding strength of the coating. This invention utilizes TiO, TiO2, and TiO2... x Multiphase synergy and adhesive bonding enhance the wear resistance, corrosion resistance and spalling resistance under conditions containing solid particles and corrosive media. It is suitable for surface protection of valve components such as ball valves and control valves, as well as wear-resistant and corrosion-resistant components, marine equipment components, or corrosion-wear coupled conditions.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating, characterized in that, include: TiC powder was ball-milled to refine it, then mixed with TiO2 powder and ball-milled again. A binder was added and ball-milled at low speed to obtain a spray-granulated slurry. After spray granulation, drying, and sieving, TiC-TiO2 spherical powder was obtained. A metal binder layer was prepared on the pretreated substrate surface, and the TiC-TiO2 spherical powder was deposited on the surface of the metal binder layer using a plasma spraying process to obtain a high-energy plasma-sprayed multiphase titanium dioxide composite coating. During plasma spraying, TiC and TiO2 undergo an in-situ redox coupling reaction, forming a TiO2-based phase containing TiO2 and TiO2. x Multiphase composite coating; wherein, 1 <x<2。 2. The method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating according to claim 1, characterized in that, The TiC powder has a particle size of 1~5 μm; the TiO2 powder has a particle size of 0.1~2 μm; and the TiO2 powder accounts for 10%~40% of the total mass of the TiC powder and TiO2 powder.

3. The method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating according to claim 1, characterized in that, The TiC-TiO2 spherical powder has a particle size of 15~53 μm and a loose packing density of 1.0-1.2 g / cm³. 3 The powder flowability is 12-18 s / 50g.

4. The method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating according to claim 1, characterized in that, The ball milling speed for TiC refinement is 300-500 r / min, and the ball milling time is 6-8 h; the ball milling time after adding TiO2 powder is 1-4 h; the ball milling speed for low-speed ball milling after adding binder is 150-250 r / min, and the ball milling time is 2-4 h; the binder is polyvinyl alcohol or polyethylene glycol, the mass of the binder is 1%-2% of the total mass of TiC powder and TiO2 powder, and the mass concentration of the binder is 40%-50%.

5. The method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating according to claim 1, characterized in that, The conditions for spray granulation include: an inlet air temperature of 170~200℃, a centrifugal frequency of 260~280 Hz, and a feed rate of 20~30 RPM.

6. The method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating according to claim 1, characterized in that, The substrate is steel, high-temperature alloy or titanium alloy; the pretreatment of the substrate includes: sandblasting roughening and cleaning of the substrate before spraying, and preheating the substrate to 300~450℃. The conditions for sandblasting roughening include: sandblasting air pressure of 0.3±0.05 MPa, sandblasting angle of 70±10°, and distance between the spray gun and the substrate surface of 100~150 mm.

7. The method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating according to claim 1, characterized in that, The metal bonding layer is a NiCr bonding layer with a thickness of 50~100 μm.

8. The method for preparing a high-energy plasma-sprayed multiphase titanium dioxide composite coating according to claim 1, characterized in that, The parameters of the plasma spraying process include: current of 300-400 A, voltage of 120-160 V, and argon flow rate of 150-220 L·min. -1 The hydrogen flow rate is 6-10 L·min -1 The spraying distance is 100-120 mm, and the powder feeding rate is 5-10 g·min. -1 .

9. A high-energy plasma-sprayed multiphase titanium dioxide composite coating, characterized in that, The high-energy plasma-sprayed multiphase titanium oxide composite coating was prepared by any one of claims 1-8, and the bonding strength of the high-energy plasma-sprayed multiphase titanium oxide composite coating was 46.4~65.8 MPa.

10. The application of the high-energy plasma-sprayed multiphase titanium oxide composite coating of claim 9 in the surface protection of valve components, wear-resistant and corrosion-resistant components, marine equipment components, or surfaces subjected to corrosion and wear coupling conditions.